Cardiac (tele)rehabilitation in routine clinical practice for patients with coronary artery disease: protocol of the REHAB + trial - van Mierlo, Rutger F. R.; Houben, Vitalis J. G.; Rikken, Sem A. O. F.; Gómez-Doblas, Juan Jose; Lozano-Torres, Jordi; van ’t Hof, Arnoud W. J. (Frontiers in Cardiovascular Medicine, 2024)
Cardiac rehabilitation programs face the challenge of suboptimal participation, despite being a level Ia recommendation. Cardiac telerehabilitation, with its potential to engage patients who might otherwise not show interest, necessitates the adaption of existing center-based cardiac rehabilitation programs to facilitate rehabilitation at home. REHAB+ is a mobile cardiac telerehabilitation program cocreated with patients and rehabilitation centers, aiming to futureproof cardiac rehabilitation and improve accessibility. The REHAB+ application enables users to remotely communicate with their coach, receive on-demand feedback on health goal progression, and reduces the need for frequent in-person meetings at the cardiac rehabilitation center. The REHAB+ study seeks to compare patient-related outcomes and characteristics of patients between those offered the option to participate in cardiac telerehabilitation and those attending center-based cardiac rehabilitation over a twelve-month period.The REHAB+ study is a multicenter, prospective, matched controlled, observational study that includes (N)STEMI patients eligible for cardiac rehabilitation. We aim to enroll 300 participants for cardiac telerehabilitation and 600 for center-based cardiac rehabilitation. Participants opting for cardiac telerehabilitation (REHAB+) will be matched with center-based cardiac rehabilitation participants. Additionally, characteristics of patients unwilling to participate in either center-based rehabilitation or telerehabilitation but are willing to share their demographics will be collected. The primary endpoint is quality of life measured with the SF-36 questionnaire at three and twelve months, with patient-related characteristics driving intervention choice as the most important secondary endpoint. Secondary endpoints include physical activity, modifiable risk factors, and digital health experience. The trial is registered at clinicaltrials.gov with registration number NCT05207072.The REHAB+ trial is unique by offering patients freedom to choose between cardiac telerehabilitation and center-based rehabilitation. The integration of digital components into cardiac rehabilitation has the potential to complement behavioral change strategies for specific patient groups. Offering patients the option of cardiac telerehabilitation next to center-based rehabilitation could enhance overall cardiac rehabilitation participation rates.